Critical Discourse of the Van Dijk Model on Roasting Marshel Widiyanto in the Mata Najwa Program Youth in Power Episode - Rojudin Rojudin; Intan Sari Ramdhani (Universitas Indraprasta PGRI, 2022)
This study discusses Marshel Widianto's roasting video broadcast on Najwa Shihab's Youtube media with the title